Effects of dairy and plant protein on growth and growth biomarkers in a piglet model. Issue 22 (1st November 2021) - Ingerslev, Anne Krog; Rasmussen, Laura; Zhou, Pan; Nørgaard, Jan Værum; Theil, Peter Kappel; Jensen, Søren Krogh; Lærke, Helle Nygaard
Abstract : Beyond a favourable amino acid composition and high digestibility, milk protein does not specifically stimulate growth via IGF-1 or insulin signalling pathways. Abstract : The increasing world population with improved living conditions has increased the demand for food protein. This has intensified the search for sustainable alternative plant-derived high-quality protein sources for human nutrition. To study the effect of plant and milk proteins on growth in weaned pigs as a model for humans, 96 weaned pigs were divided into 48 pens and fed one of 4 different diets for 3 weeks. The dietary protein originated from either 50% rice + 50% 00-rapeseed protein (RICE + RAPE), 50% milk protein (MPC) + 50% 00-rapeseed protein (MPC + RAPE), 50% milk + 50% rice protein (MPC + RICE), or 100% MPC, and were supplemented with crystalline amino acids to meet the amino acid requirements. Weekly feed intake and body weights were recorded and after 3 weeks, a blood sample was taken 1 hour after a fixed meal, while organ weights were measured, and liver- and muscle tissue, and bone samples were collected at euthanasia. All pigs had a high daily gain and a low feed-to-gain ratio (F : G, feed intake per kg weight gain), but feed intake and daily gain was lowest and F : G highest in the RICE + RAPE diet. Metacarpal bones were longer and heavier in MPC + RICE and MPC fed pigs compared to pigs fed diet RICE + RAPE ( P < 0.05), and intermediate in MPC + RAPE fed pigs, with no differences in bone thickness ( P > 0.05). Plasma levels of all essential amino acids except Cys and Lys decreased markedly when fed a diet containing only plant protein. The differences were not associated with differences in plasma insulin or IGF-1, nor in the abundance of mRNA related to growth in liver and longissimus dorsi muscle. In conclusion, the growth of piglets fed a combination of milk and rice protein did not differ from the pure dairy-based diet, whereas the pure plant-based diet consisting of rice and rapeseed protein led to reduced growth. This was most likely caused by a lower feed intake and a lower than expected amino acid digestibility of the 00-rapeseed protein. There were no indications that the milk protein, beyond a favourable amino acid composition and high digestibility, specifically stimulated growth factors or other biomarkers of growth via the IGF-1 and insulin signalling pathways.